The social dynamics of community development in a suburban Johannesburg public open space: Verity Park - Hoenderdos, René (Environnement urbain)

(untitled) (Institut National de Recherche Scientifique Centre Urbanisation Culture et Société, 2016)
The use of a public space in suburban Johannesburg, South Africa, is the main focus of this research. The study area is Verity Park, a small park located in the neighbourhood of Parkhurst. The park is used by the residents of the area and the users are from a diversity of genders, ages, socio-economic and cultural backgrounds. Through an examination of Lefebvre’s ‘right to the city’ and his theories about the production of space, this research looks at how the park contributes to the development and maintenance of community.